An examined life politics and principles - Sim, Kwang Yang 1948-2014 (Strategic Information and Research Development Centre, 2020)
Sim Kwang Yang (1948-2014) was known as SKY to generations of readers and political admirers. SKY was a hermeneutic philosopher, a three-term MP for Bandar Kuching, and a columnist for Malaysiakini, The Nut Graph, and many other national and Sarawakian newspapers, writing in English and Chinese. Sarawak's SKY meant light, and fresh air, to Malaysian society. He was Anak Sarawak, Bangsa Malaysia: a national leader respected by political allies and opponents alike. SKY's principles of universal concern and social justice remained solid, throughout four decades of political education and writing. SKY was incorruptible. His idealism shone through the cynicism of Malaysian politics. His essays, full of intellectual curiosity and humour, offer us inspiration and insight today, at a time when sophistry and despair in our national life seem ever more prevalent.